Sketching sounds – Kinds of listening and their functions in designing. (July 2015) - Nykänen, Arne; Wingstedt, Johnny; Sundhage, Johan; Mohlin, Peter
Abstract : In this work, the use of sketching in sound design was studied. Based on Schon and Wiggins' model of how designers use sketching to see, move, and see again, we suggest that sound design evolves through a similar process requiring listening, moving, and listening again. This is facilitated by considering sounds as sketches. A case was followed in which six designers were asked to design a sound logotype. Processes and interactions were studied. The results suggest that sound design can be considered as a listen – move – listen process. Sound design is a conversation with sounding material, crucially dependent on listening. To assist in this, a computer interface was developed. Analysis of its use suggests that it supported co-designing. Highlights: Sound design evolves through a listening – moving – listening process. Using sounds as sketches facilitates such a process. New tools and methods for sketching sound are needed. A computer interface for co-creation of sound sketches was developed.